2021
DOI: 10.1051/e3sconf/202124601004
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Co2 Concentration in A Classroom During The Covid-19 Safety Measures

Abstract: The COVID-19 crisis has affected the process of how the study procedures are organized at schools in Latvia. Three different options were available for the school to choose from. However, most schools have opted for option A which states that the classes are organized face-to-face but various safety measures must be ensured. Each class or group is equated to a closed set where there are no distance requirements. In turn, the distance between the classes must be observed. This means that students stay in the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…This showed that the effect of this stop was not significant on the IAQ during the test. The same effect was also found in the work of Zemitis et al (2021) . In relation to air renewals, these were 9.01 with a clean air supply per occupant of 42.39 l/s per person (values well above the minimum recommendations to guarantee adequate air quality and minimise COVID-19 infections) ( Allen et al, 2020 ; Minguillón et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…This showed that the effect of this stop was not significant on the IAQ during the test. The same effect was also found in the work of Zemitis et al (2021) . In relation to air renewals, these were 9.01 with a clean air supply per occupant of 42.39 l/s per person (values well above the minimum recommendations to guarantee adequate air quality and minimise COVID-19 infections) ( Allen et al, 2020 ; Minguillón et al, 2020 ).…”
Section: Resultssupporting
confidence: 87%
“…These values were very similar to those obtained in this work ( Villanueva et al, 2021 ). However, in the case of the research carried out in schools in Switzerland and Latvia, CO 2 concentration was much higher, with average values of around 2000 ppm, and consequently air renewal in both cases was insufficient ( Vassella et al, 2021 ; Zemitis et al, 2021 ). Comparing CO 2 concentrations, it can be verified that ventilation conditions in the present study are significantly better than those reported in most of the existing literature.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As determined by the European branch of the World Health Organization [35] and the American Society of Heating, Refrigeration and Air-conditioning Engineers [47], the permissible concentration of carbon dioxide in closed spaces is 1000 ppm (0.1%), which is a requirement of the so-called hygienic minimum. This acceptable limit is often exceeded, reaching (in the classrooms) such values as high as 4000 ppm [28,36,[48][49][50][51]. The presented phenomena are very common in education buildings with natural (gravity) ventilation systems dominant in Poland, as well as in the countries with similar climate.…”
Section: Introductionmentioning
confidence: 95%
“…In the pre-pandemic period, CO 2 measurement helped improve academic performance in schools and colleges [ 24 ] and, sporadically, control infectious diseases [ 25 ]. Due to the COVID-19 pandemic, CO 2 measurement has become one of the preferred preventive strategies to reduce the risk of contagion by aerosols [ 22 , 26 , 27 ]. The direct measurement of aerosols to determine the risk of contagion by SARS-CoV-2 is highly complex and expensive since it requires highly specialized equipment.…”
Section: Introductionmentioning
confidence: 99%